Weather and US - Chappell, Rachel; Nang Chan Yeema (Bethany, MO USA Fitzgerald Books, 2007)
Illustrations and text introduce various types of weather and climate, including how it affects our everyday decisions and how we feel.
Keywords: Juvenile Nonfiction